2006
DOI: 10.1158/1078-0432.ccr-05-0750
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microflora and digestive toxicity of irinotecan in mice.

Abstract: Purpose: Delayed diarrhea is the most important side effect of irinotecan. The aim of this study was to investigate the role of intestinal microflora on the induction of systemic and intestinal toxicity and diarrhea, studying germ-free and holoxenic mice i.p. injected with irinotecan. Experimental Design: To evaluate the lethal dose, starting with 100 mg/kg/4 d, we treated the holoxenic mice with100, 80, and 60 mg/kg/4 d and germ-free mice with 60, 80,100, and150 mg/ kg/4 d. We recorded the percentage of dead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 22 publications
3
70
0
Order By: Relevance
“…A dosing scheme of 50 mg/kg/day, once daily for 9 days, was chosen with the intention of accelerating the onset of diarrhea while preventing death. As outlined previously, 50 mg/kg CPT-11 in mice is roughly equivalent to the 5 mg/kg typical human CPT-11 dose based on differences in body surface area (Brandi et al, 2006;Reagan-Shaw et al, 2008). GI symptoms in group 3 started as early as day 2 and up to day 10 and included decreased appetite, bowel movements, mobility, and body weight.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…A dosing scheme of 50 mg/kg/day, once daily for 9 days, was chosen with the intention of accelerating the onset of diarrhea while preventing death. As outlined previously, 50 mg/kg CPT-11 in mice is roughly equivalent to the 5 mg/kg typical human CPT-11 dose based on differences in body surface area (Brandi et al, 2006;Reagan-Shaw et al, 2008). GI symptoms in group 3 started as early as day 2 and up to day 10 and included decreased appetite, bowel movements, mobility, and body weight.…”
Section: Methodsmentioning
confidence: 93%
“…It also appears that widespread use of antibiotics may have subtle but serious side effects on human health (Maurice et al, 2013). Additionally, for patients with colorectal cancer, the use of antibiotics to treat CPT-11-induced toxicity may lead to the increased prevalence of subdominant bacterial species with higher overall b-glucuronidase activity in the GI tract and thus, increased toxicity (Brandi et al, 2006). Studies have also shown that the long-term use of neomycin in mice leads to increased serum bilirubin that may interfere with proper hepatic CPT-11 metabolism (Vítek et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irinotecan lethal dose is more than twice higher in the second group, which also exhibited significantly less diarrhoea. Intestinal damage as shown by histological examination reflected bacterial distribution along the gut, in particular it was negligible in germ-free animals treated at 60 mg kg À1 d À1 for 4 days, the lethal dose for holoxenic controls (Brandi et al, 2006).…”
Section: Sirmentioning
confidence: 97%
“…Irinotecan lethal dose is more than twice higher in the second group, which also exhibited significantly less diarrhoea. Intestinal damage as shown by histological examination reflected bacterial distribution along the gut, in particular it was negligible in germ-free animals treated at 60 mg kg À1 d À1 for 4 days, the lethal dose for holoxenic controls (Brandi et al, 2006).The poor predictive value for diarrhoea of the genetic loci studied by Rouits et al is therefore not surprising. In humans, intestinal microflora composition is quite stable along life and host-specific, representing a sort of adjunctive fingerprint.…”
mentioning
confidence: 92%